Organic agriculture in Kyrgyzstan: experiences with implementing participatory guarantee systems - Taranov, Igor; Kawabata, Yoshiko (Frontiers in Sustainable Food Systems, 2024)
Organic farming plays a pivotal role in the recent initiative to develop a sustainable economy in the Kyrgyz Republic (Kyrgyzstan). Key national policy documents support a green agricultural development path and highlight the potential of organic agricultural production and exports. This study therefore elicited perspectives on organic farming from organic farmers and stakeholders in Kyrgyzstan, focusing on the role of Participatory Guarantee Systems (PGS) in its promotion. Interviews held with these two groups revealed that, whereas organic farmers are primarily motivated by personal and family health concerns despite unfair market prices and insufficient governmental support, stakeholders prioritize environmental protection and view the inclusion of PGS in national legislation as a milestone in organic certification. Also, the recent COVID-19 pandemic has influenced farmers’ motivation for organic conversion owing to increased health concerns and food safety. The study’s findings highlight the potential of PGS to foster cooperation within local communities and familiarize farmers with organic principles and methods. PGS can be used as a framework to strengthen social and economic links within local farming communities and preserve traditional local knowledge and farming practices that are crucial for climate change mitigation and sustainable agriculture. Moreover, PGS may be applied in business as a model for establishing collaboration with other sectors at both domestic and international levels. The findings underscore the significance of PGS in the sustainable development of organic farming in Kyrgyzstan. However, challenges such as inadequate infrastructure and knowledge need to be addressed through the government’s increased involvement and through cooperation among actors within the organic sector. Overall, the PGS approach may be used by policymakers as a relevant and feasible tool for introducing organic principles within agricultural policies and disseminating organic practices across the country.